Impact of Trichoderma afroharzianum infection on fresh matter content and grain quality in maize - Pfordt, Annette; Steffens, Lara Änne; Raz, Tom; Naumann, Marcel (Frontiers in Plant Science, 2024)
Trichoderma afroharzianum, a ubiquitous soil-borne fungus found on plant roots and decaying residues, displays competitive traits and mycoparasitic behavior against diverse microorganisms. Selected strains of this fungus are known in agriculture for their beneficial effects on plant growth and as bio-fungicides. However, recent findings have pinpointed Trichoderma afroharzianum as the causal agent behind maize ear rot disease in Europe since 2018, notably impacting maize cobs in Germany, France, and Italy. This study aims to evaluate the severity of Trichoderma ear rot disease on maize fresh matter content and specific quality parameters under semi-field conditions. Two distinct maize varieties were artificially inoculated with a pathogenic Trichoderma isolate at the flowering stage using needle pin or silk channel methods. Disease severity was assessed visually at the time of harvest based on the percentage of infected kernels according to EPPO Guidelines (PP 1/285). Fresh matter content and quality parameters such as alpha-amylase activity, C/N ratio, water, and sugar content were analyzed. Results showed that needle pin inoculation led to higher disease severity (60%) compared to silk channel inoculation (39%). Cob weight decreased significantly at the highest disease severity level by up to 50% compared to control plants. In both varieties, alpha-amylase activity increased significantly with higher Trichoderma disease severity, resulting in starch degradation and increased glucose release. The germination rate was severely affected by the infection, with only 22% of grains germinating, and the seedlings showed shortened and deformed growth. This is the first report on Trichoderma ear rot infection and its effect on fresh matter content and quality parameters in maize after artificial inoculation under field conditions. The results address an important knowledge gap and provide valuable insights into the infection pathway and impact on maize quality.